If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2x + -9 = 3x + -17 Reorder the terms: -9 + 5x + -2x = 3x + -17 Combine like terms: 5x + -2x = 3x -9 + 3x = 3x + -17 Reorder the terms: -9 + 3x = -17 + 3x Add '-3x' to each side of the equation. -9 + 3x + -3x = -17 + 3x + -3x Combine like terms: 3x + -3x = 0 -9 + 0 = -17 + 3x + -3x -9 = -17 + 3x + -3x Combine like terms: 3x + -3x = 0 -9 = -17 + 0 -9 = -17 Solving -9 = -17 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 36-a=36 | | 3x+25=28 | | 7e^8x=1015 | | 3e^7x=756 | | d(x)=0.04x^2+2x | | 7y-34+9x-4=180 | | 0.6(2.4a-1.4)=6 | | 6(x-1)-4=14 | | 3y+7=3y-12 | | 12-.5x=7 | | (34+13i)-(-2-17i)+(16+25i)=0 | | x+10y=-8 | | 7+m=20 | | p^2=6p+16 | | 8(t+8)=96 | | 9y+28=120 | | 3(5x+2)=8x-5 | | -1+2x=-7 | | 3x+7y-21=10xy+(-21) | | 5.75x-10=9.25+2 | | -6.1n-3.9n= | | 13y=4y+36 | | 13.50/20= | | 10y+4=124 | | 36=3(x+6) | | 9x^2-6x+k=0 | | i(3+2i)(3+2i)=0 | | 15+n=15 | | 5n+4x=3v | | 9=-5(w+6) | | 52+2x=56 | | V=-12f |